Emerging Technologies in Data Mining and Information Security Proceedings of IEMIS 2018, Volume 3 - Abraham, Ajith; Dutta, Paramartha; Mandal, Jyotsna Kumar; Bhattacharya, Abhishek; Dutta, Soumi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book features research papers presented at the International Conference on Emerging Technologies in Data Mining and Information Security (IEMIS 2018) held at the University of Engineering & Management, Kolkata, India, on February 23-25, 2018. It comprises high-quality research by academics and industrial experts in the field of computing and communication, including full-length papers, research-in-progress papers, case studies related to all the areas of data mining, machine learning, IoT and information security.
Proposed Memory Allocation Algorithm for NUMA based Soft Real Time Operating System -- Mathematical Model of Fog Computing Architecture for IoT Micro-Services -- Analysis of Attention Level of Human Body in Different Form -- Analytical Survey on Standards of Internet of Things Framework & Platforms -- A Predictive Resource Management Technique in Grid -- Cryptanalysis of a Chaotic Key based Image Encryption Scheme -- Blind RGB Image Steganography using Discrete Cosine Transformation -- Wavelet and Pyramid Histogram Features for Image based Leaf Detection -- Automated Detection of Glaucoma using Image Processing Techniques -- Chemical Reaction Optimization Algorithm for Word Detection using Pictorial Structure -- Secure Remote Patient Monitoring with Location Based Services -- Development of Joint Intelligent Millimeter Wave Sensing and Communication -- Machine Learning for Mining Imbalanced Data -- Key Feature Extraction and Machine Learning Based Automatic Text Summarization -- Prediction of Gold Price Movement Using Geopolitical Risk as a Factor.
Keywords: Computational intelligence; Artificial intelligence; Data protection; Computational Intelligence; Artificial Intelligence; Data and Information Security